MENINGKATKAN INTERAKSI SOSIAL SISWA MELALUI LAYANAN BIMBINGAN KELOMPOK TEKNIK ROLE PLAYING PADA SISWA KELAS VIII SMP NEGERI 1 PERBAUNGAN T.A 2015/2016 - Rizky Yusrina Siregar; Dr. Nur’aini, MS Dr. Nur’aini, MS (Faculty of Psychology, Universitas Medan Area, 2016)
The purpose of this study is to help improve students' social interaction through group counseling service engineering role playing in class VIII SMP Negeri 1 Perbaungan T.A 2015/2016. This research uses research PTBK (Action Research Counseling) with two cycles, the first cycle and the second cycle consisting of planning, action, observation, reflection and evaluation. Data collection to encompass students who have low social interaction by using questionnaires of social interaction, in the form of an ordinal scale with Likert scale form. The subject of this study is 6 students who have social interaction of students is low. Analysis of the data used in analysis techniques percentage. The results showed an increase in the students' social interaction after the administration of guidance services group role playing techniques. In the first cycle students' results increased social interaction by 50%. And the second cycle students hasiln increased social interaction improved to 83.3%. From the results of the study concluded that the hypothesis can be accepted is by implementing role playing group counseling services can improve social interaction class VIII SMP Negeri 1 Perbaungan T.A 2015/2016.